ETHICAL PRINCIPLES FOR MEDICAL RESEARCH INVOLVING HUMAN SUBJECTS. World medical association, declaration of Helsinki - article editorial (Union of pediatricians of Russia, 2007)
Adopted by the 18th wma general assembly Helsinki, Finalnd, June 1964 and amended by the 29 th WMA general assembly, Tokyo, Japan, October 1975; 35 th WMA general assembly, venice, Italy, October 1983; 41st WMA general assembly, Hongkong, September 1989; 48th WMA general assembly, somerset west, republic of south Africa, October 1996 and the 52nd WMA genaeral assembly, Edinburgh, Scotland, October 2000.